Usability Testing of the PACE-App to Support Family Caregivers in Managing Pain for People With Dementia. - Chi, Nai-Ching; Nguyen, Kristy; Shanahan, Angela; Demir, Ibrahim; Fu, Ying-Kai; Chi, Chih-Lin; Perkhounkova, Yelena; Hein, Maria; Buckwalter, Kathleen; Wolf, Michael; Williams, Kristine; Herr, Keela (Gerontologist, 2025)
Background and Objectives Pain management is often suboptimal in individuals with dementia, and their family caregivers are tasked with supporting pain management despite limited preparation. The web-based PACE-app (PAin Control Enhancement) was designed to assist caregivers in managing pain for individuals with dementia. This study aimed to evaluate the usability of the PACE-app. Research Design and Methods A convergent parallel mixed-methods design was used to evaluate the PACE-app's usability with 16 family caregivers and 6 healthcare professionals. Quantitative data were collected using the Post-Study System Usability Questionnaire (PSSUQ), and qualitative data were gathered through guided-app reviews and semistructured interviews. Quantitative data were analyzed descriptively, and qualitative data were thematically coded. Results The PSSUQ results indicated that both family caregivers and healthcare professionals had a highly positive experience with the PACE-app: overall scores (2.01 vs 1.68), system usefulness (1.76 vs 1.68), information quality (1.98 vs 1.80), interface quality (2.30 vs 1.60), and satisfaction (2.00 vs 1.60) were rated on a 1–7 scale (with lower scores indicating better usability). Qualitative findings supported these results, with participants endorsing the PACE-app's usefulness, ease of use, learnability, effective information presentation, aesthetics, clear layout, and overall satisfaction. Participants also provided valuable feedback for improving information quality (enhancing clarity) and interface quality (real-time coaching on pain management). Discussion and Implications The study demonstrated favorable usability and strong satisfaction among family caregivers and healthcare professionals using the PACE-app. Incorporating participants' suggestions will guide enhancements to the app's information and interface, ensuring it better meets users' needs.